Analisis Lalu Lintas Harian Rata – Rata (LHR) dalam Menghindari Kecelakaan - Gendoet Indarto Wibisono; Fajar Eka Ramadan; Arif Hernawan Fajar (Institut Transportasi dan Logistik Trisakti, 2019)
PT. Jasa Marga (Persero) Tbk is one of the Toll Road Service Provider Operators in Indonesia. Jasa Marga has been trusted to be responsible for toll road construction in Indonesia. With the large number of road growth, there will also be more toll roads to connect several regions in Indonesia. The purpose of this study is to determine the Average Daily Traffic (LHR) of the accident rate, to solve the problem, the author used 2 (two) methods, the first method of collecting data in the form of field data (field research) and documents review (based on the data from the company). The second method was data analysis with the basic calculation of Accident Rate. The results from the analysis show there is a contribution from the Average Daily Traffic (LHR) (X) of 27.04% to the accident rate (Jakarta - Cikampek Toll Road) (Y) and the rest 72.96% is the influence of other factors besides the Average Daily Traffic average (LHR).